WATER SECURITY IN ECOLOGICAL POLITICS DURING COVID-19 PANDEMIC ERA - Muhammad Yunus Zulkifli (Sociae Polites, 2021)
The major challenges related to water security today are efforts to reduce flood risk; and efforts to increase water supply for communities, industry and agriculture. The ecohydrological approach is present as a solution to these two challenges. On the other hand, the ecological problem with the issue of water security in it has developed over time and awaits real action by the government. In a political framework, ecological issues have been considered marginal and lacking in priority instead of being dominated by other fields, such as economy, law, and infrastructure. In fact, the government is to be committed to promoting eco-friendly development. In the current COVID-19 pandemic, leadership that cares about the environment as a manifestation of ecological politics is a necessity, and is expected to be present both substantially and factually. With the spirit of ecological leadership, strengthening the environmental sector will be on par with other sectors. Keywords: water security, eco-friendly development, ecological politics, ecological leadership.